Association between some serum oxidative stress biomarkers and lipid profile in type 2 diabetic patients in Erbil City - Hemn Jameel Majeed; Gulzar Ismael Ibrahim; Pshtiwan Abdullah Yousif; Saman Muhsin Abdulkareem4 (Zanco Journal of Pure and Applied Sciences, 2021)
Increased oxidative stress appears to be a negative factor leading to insulin resistance, dyslipidemia, β-cell dysfunction, impaired glucose tolerance, and ultimately leading to type 2 diabetes mellitus. The aim of the study is to investigate some serum oxidative biomarkers, lipids, and their association with hyperglycemia in patients with type 2 diabetes. The 100 participants (50 patients with type 2 diabetes mellitus and 50 healthy individuals) were enrolled in the present study. Anthropometric measures, serum fasting blood sugar, glycated hemoglobin, oxidative biomarkers, and serum lipid profiles were evaluated. The results showed that the level of malondialdehyde, fasting blood sugar, glycated hemoglobin, and lipid profile in patients with type 2 diabetes is higher than those in the control group, while nitric oxide was lower in diabetic than those in the control group. There are also insignificant changes in fasting blood sugar and glycated hemoglobin between baseline and after 3 months follow up. The results showed no linear relationship between oxidative damage and abnormal lipid profiles in patients with type 2 diabetes. It can be concluded that the serum level of malondialdehyde and nitric oxide, along with lipid parameters in patients with type 2 diabetes, can be a useful tool for monitoring of type 2 diabetes.